A porous thermal insulation and sound-absorbing aerogel, its preparation method and application
By adding a combination of vanadium titanic acid calcium line and bacterial cellulose to the porous sound absorption material to form a porous thermal heating sound suction gas gel, it solves the problem of insufficient vocal absorption in the low -frequency band in the low -frequency band, and realizes excellent. Low -low frequency sound absorption performance and thermal insulation effect.
Patent Information
- Application Number
- CN202310597325.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-05-25
AI Technical Summary
The sound absorption properties of the conventional oriented porous sound absorbing materials are poor in the middle and low frequency bands, especially when the incident direction of the sound wave is perpendicular to the orientation of the sound absorbing material holes, the sound absorption properties of the material are further reduced.
By adjusting the amount of titanium titanic acid in the raw material system, the amount of polyvinyl alcohol and bacterial cellulose is combined to form a porous heat suction gas gel. The calcium titanate calcium line is tangled with bacterial cellulose, and it is evenly scattered in polyvinyl to form a complex tunnel structure to improve the low -frequency sound absorption performance of the material.
It has a high sound absorption performance in the low frequency band. Even when the direction of the sound wave incident and the orientation of the material hole can be maintained, it can maintain a good sound absorption effect. At the same time, the heat source is effectively isolated and the heating performance of the material is improved.
Smart Images

Figure CN116622176B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a porous heat-insulating sound-absorbing aerogel and a preparation method and application thereof, belonging to the technical field of heat-insulating sound-absorbing materials. Background Art
[0002] With the development of industrialization and urbanization, reducing the noisy noise in life and improving the temperature suitability of the human body will help to obtain better housing comfort and transportation driving experience. Traditional insulation and sound-absorbing materials include: glass fiber, polyurethane foam, asbestos, etc. These materials often have porous characteristics inside. The advancing sound waves rub against the complex channels inside them, and the mechanical energy is converted into heat energy to achieve the dissipation of noise. At the same time, there is a large amount of air in the high-porosity sound-absorbing material, which can effectively reduce the thermal conductivity of the solid and achieve the insulation effect. The sound absorption of the existing oriented porous materials in the low-frequency band is significantly inferior to that in the high-frequency band, especially when the incident direction of the sound wave is perpendicular to the orientation of the sound-absorbing material hole, which makes the sound absorption of the porous sound-absorbing material in the low-frequency band worse. However, many devices in life can generate low-frequency noise, such as compressors, exhaust fans, boilers, washing machines, etc., and the incident direction of the sound wave is non-directional. In order to improve the low-frequency absorption effect of traditional oriented porous sound-absorbing materials, it is necessary to increase the material thickness and the cavity at the back of the material, which limits its application in more scenarios. Summary of the invention
[0003] In view of the problems existing in the prior art, the first object of the present invention is to provide an oriented porous heat-insulating sound-absorbing aerogel with low density, high porosity, thin thickness, excellent sound absorption effect, and effective insulation of heat sources. By adjusting the amount of barium calcium zirconate titanate wire added in the raw material system and the sound-absorbing material, the sound absorption performance of the material can be regulated and controlled, and high-efficiency sound absorption within a certain frequency band can be achieved. When the oriented porous heat-insulating sound-absorbing aerogel provided by the present invention is used as a sound-absorbing material, it can still have high sound absorption performance in the low frequency band even when the incident direction of the sound wave is perpendicular to the orientation of the sound-absorbing material pores.
[0004] The second object of the present invention is to provide a method for preparing the porous thermal insulation and sound absorbing aerogel prepared by the above preparation method.
[0005] The third object of the present invention is to provide an application of a porous thermal insulation and sound absorption aerogel.
[0006] In order to achieve the above objectives, the following technical solutions are adopted:
[0007] The invention provides a porous heat-insulating sound-absorbing aerogel. The porous heat-insulating sound-absorbing aerogel comprises polyvinyl alcohol, bacterial cellulose and barium calcium zirconate titanate wires. The barium calcium zirconate titanate wires and the bacterial cellulose are entangled with each other and dispersed in the polyvinyl alcohol.
[0008] The porous heat-insulating sound-absorbing aerogel provided by the present invention uses polyvinyl alcohol as a polymer matrix framework in the system, and barium calcium zirconate titanate wires and bacterial cellulose are entangled with each other and uniformly dispersed in the matrix. The inventors found that the addition of barium calcium zirconate titanate wires can enhance the peak value of the sound absorption coefficient of 2000-3000Hz, so that the porous heat-insulating sound-absorbing aerogel of the present invention has excellent medium and low frequency sound absorption performance. At the same time, the barium calcium zirconate titanate wires and bacterial cellulose are entangled with each other to form complex channels in the material. Sound waves are blocked and dissipated when advancing in the aerogel, further realizing the dissipation of noise and improving the medium and low frequency sound absorption performance.
[0009] In a preferred embodiment, the calcium barium zirconate titanate wires are in the shape of short rods, and the bacterial cellulose is in the shape of filaments.
[0010] In a preferred embodiment, the calcium barium zirconate titanate wire is made by electrospinning.
[0011] In a preferred embodiment, in the porous heat-insulating sound-absorbing aerogel, the mass ratio of polyvinyl alcohol: bacterial cellulose: barium zirconate calcium wire is 1-7:1-5:1-8, preferably 6:5:1-3.
[0012] The inventors found that by controlling the amount of each substance in the porous insulating sound-absorbing aerogel within the above range, the final porous insulating sound-absorbing aerogel has the best performance. If there is too much bacterial cellulose, the mechanical properties of the porous insulating sound-absorbing aerogel will be reduced. If too little electrospun barium calcium zirconate titanate wire is added, the improvement in the medium and low frequency sound absorption performance is not obvious. However, adding too much electrospun barium calcium zirconate titanate wire will lead to a decrease in the porosity of the aerogel finished product, which is not conducive to the improvement of the sound absorption and thermal insulation performance.
[0013] In a preferred embodiment, the thickness of the porous heat-insulating sound-absorbing aerogel is 5 to 10 mm. The inventors have found that the sound absorption effect is optimal when the thickness of the porous heat-insulating sound-absorbing aerogel is controlled within the above range.
[0014] In a preferred embodiment, the porous structure of the porous thermal insulation sound absorbing aerogel is an oriented porous structure. The inventors have found that the oriented porous structure can further enhance the sound absorption effect of the porous thermal insulation sound absorbing aerogel.
[0015] The present invention also provides a method for preparing a porous thermal insulation sound-absorbing aerogel, comprising adding barium calcium zirconate titanate wire into a solvent, then adding a dispersant to mix to obtain a mixed solution, adding a polyvinyl alcohol aqueous solution to the mixed solution to mix to obtain a ceramic slurry, then mixing the ceramic slurry with a bacterial cellulose aqueous dispersion to obtain a mixed slurry, pouring the mixed slurry into a mold, then directionally freezing it in a directional temperature field, and then freeze-drying it to obtain a porous thermal insulation sound-absorbing aerogel.
[0016] In a preferred embodiment, the solvent is selected from at least one of deionized water and anhydrous ethanol.
[0017] In a preferred embodiment, the dispersant is selected from at least one of ammonium citrate, tetramethylammonium hydroxide, ammonium polyacrylate, and polyacrylate.
[0018] In a preferred embodiment, the mass fraction of the dispersant in the mixed solution is 0.05-0.2%.
[0019] In a preferred embodiment, in the mixed solution, the mass fraction of calcium barium zirconate titanate wire is 0.1-2%, preferably 0.2-1%.
[0020] In a preferred embodiment, the mass fraction of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 3-8%.
[0021] In a preferred embodiment, the mass fraction of bacterial cellulose in the bacterial cellulose aqueous dispersion is 0.65-0.8%.
[0022] In a preferred embodiment, the mass volume ratio of the mixed solution to the polyvinyl alcohol aqueous solution is 10-15 g:2-8 mL, preferably 11-13 g:4-6 mL.
[0023] In a preferred embodiment, the mass ratio of the ceramic slurry to the bacterial cellulose aqueous dispersion is 10-15:20-30; preferably 11-13:20-25.
[0024] In a preferred embodiment, during the directional freezing, the cold end of the directional freezing temperature field is set to -196 to -20°C, the hot end is set to room temperature, and the directional freezing time is 10 to 30 minutes.
[0025] At this time, ice crystals will form at the bottom near the cold end, and the ice crystals will grow in a directional manner toward the hot end. Ceramics and organic matter will be pushed to both sides due to the growth of ice crystals, eventually forming a lamellar structure.
[0026] In a preferred embodiment, the freeze drying temperature is -60 to 0°C, the vacuum degree is 1 to 100 Pa, and the freeze drying time is 24 to 72 hours. During the freeze drying process, the material will be placed in a vacuum environment, and the ice in the system will be removed in the form of sublimation, and finally an oriented porous insulating sound absorbing aerogel is prepared.
[0027] In a preferred embodiment, the preparation method of the barium calcium zirconate titanate wire is: adding polyvinyl pyrrolidone to the barium calcium zirconate titanate sol to obtain a mixture, electrospinning the mixture to obtain a barium calcium zirconate titanate wire film, and sintering the barium calcium zirconate titanate wire film to obtain the barium calcium zirconate titanate wire.
[0028] Further preferably, in the mixture, the solid-liquid mass-to-volume ratio of polyvinyl pyrrolidone to barium calcium zirconate titanate sol is (0.2-0.7) g:10 mL.
[0029] In actual operation, polyvinyl pyrrolidone is added to the barium calcium zirconate titanate sol, and the mixture is fully stirred under heating conditions until the polyvinyl pyrrolidone is completely dissolved.
[0030] Further preferably, during the electrospinning, the feeding speed is 0.8-1.5 mL / h. If the feeding speed is too low, the spinning process is easily interrupted, and if the feeding speed is too fast, the solution cannot be fully attracted by the electric field, resulting in a waste of solution.
[0031] Further preferably, during the electrostatic spinning, the voltage in the electric field is 8 to 15 kV. If the applied electric field voltage is too low, liquid droplets will be generated in the obtained barium calcium titanate electrostatically spun barium calcium zirconate titanate wire, affecting its microscopic morphology. If the applied voltage is too high, the solvent in the fiber cannot be fully volatilized, resulting in failure of nanofiber formation.
[0032] Further preferably, the sintering system is to first heat the temperature to 280-400°C at a heating rate of 1-3°C / min and keep it at that temperature for 0.5-2.5h, then heat the temperature to 700-850°C at a heating rate of 1-3° / min, keep it at that temperature for 0.5-2.5h, and finally cool it with the furnace.
[0033] The present invention also provides an application of a porous heat-insulating sound-absorbing aerogel, wherein the porous heat-insulating sound-absorbing aerogel is used as a sound-absorbing material.
[0034] Beneficial Effects
[0035] The present invention provides a porous heat-insulating sound-absorbing aerogel, in which polyvinyl alcohol serves as a polymer matrix framework in the system, and barium calcium zirconate titanate wires and bacterial cellulose are entangled with each other and uniformly dispersed in the matrix. The inventors have found that the addition of barium calcium zirconate titanate wires can promote the enhancement of the peak value of the sound absorption coefficient at 2000-3000 Hz, so that the porous heat-insulating sound-absorbing aerogel of the present invention has excellent medium and low frequency sound absorption performance. At the same time, the barium calcium zirconate titanate wires and bacterial cellulose are entangled with each other to form complex pores in the material, and sound waves are blocked and dissipated when advancing in the aerogel, thereby further realizing the dissipation of noise and improving the medium and low frequency sound absorption performance.
[0036] During the preparation process, the present invention sets a directional temperature field and then freeze-dries to sublimate ice crystals in the system, and finally obtains an oriented porous heat-insulating sound-absorbing aerogel. The material has a porous structure and low density. In the preferred embodiment, the oriented porous heat-insulating sound-absorbing aerogel provided by the present invention has a porosity of 98.6% and a density of only 0.018 g / cm 3 . The high porosity allows the material to be filled with air, effectively reducing the thermal conductivity of the material and achieving a heat-insulating effect. At the same time, the aerogel can effectively absorb sound energy and hinder the propagation of noise. In the frequency band of 800-6300Hz, the oriented porous insulation sound-absorbing aerogel with a thickness of 5mm can produce an absorption peak with a sound absorption coefficient close to 0.9. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is the SEM image of the oriented porous thermal insulation and sound absorbing aerogel prepared by the method in Comparative Example 1.
[0038] Figure 2 This is a curve showing how the sound absorption coefficient changes with frequency when the aerogel is prepared using the method in Comparative Example 1 and the direction of the oriented pores is parallel to the incident direction of the sound wave.
[0039] Figure 3 This is a curve showing how the sound absorption coefficient changes with frequency when the aerogel is prepared using the method in Comparative Example 2 and the direction of the oriented holes is perpendicular to the incident direction of the sound wave.
[0040] Figure 4 This is a curve showing how the sound absorption coefficient changes with frequency when the aerogel is prepared using the method in Comparative Example 3 and the direction of the oriented holes is parallel to the incident direction of the sound wave.
[0041] Figure 5 This is the SEM image of the electrospun barium calcium zirconate titanate wire prepared in Example 1.
[0042] Figure 6 The aerogel is prepared by the method in Example 1. When the orientation hole direction is parallel to the incident direction of the sound wave, the sound absorption coefficient changes with the frequency band.
[0043] Figure 7 The aerogel is prepared by the method in Example 1. When the orientation hole direction is perpendicular to the incident direction of the sound wave, the sound absorption coefficient changes with the frequency band.
[0044] Figure 8 The aerogel is prepared by the method in Example 2. When the orientation hole direction is perpendicular to the incident direction of the sound wave, the sound absorption coefficient changes with the frequency band. DETAILED DESCRIPTION
[0045] In the following examples, the preparation methods of polyvinyl alcohol aqueous solutions are all like this:
[0046] Take 5 g of polyvinyl alcohol and add it to 95 g of deionized water. Stir it in an 85°C oil bath for 1 h until the solution becomes clear.
[0047] Comparative Example 1
[0048] 23.04g of 0.8% bacterial cellulose aqueous dispersion was mixed with 4.608mL of polyvinyl alcohol aqueous solution, stirred thoroughly, and then poured into a round mold with a height of 5.5mm. When the hot and cold plates dropped to -100°C, the mold was placed on the hot and cold plates and frozen for 30 minutes to obtain a white columnar frozen block. After the mold was removed, the frozen block was placed at -50°C and freeze-dried at a vacuum degree of 10Pa for 72 hours to obtain an oriented porous insulating sound-absorbing aerogel.
[0049] Figure 1 This is a SEM image of the oriented porous heat-insulating sound-absorbing aerogel prepared by the method in Comparative Example 1. From the microscopic morphology, the aerogel has an oriented porous structure, which can effectively attenuate incident sound energy and enhance the sound absorption performance of the material.
[0050] Figure 2 The aerogel was prepared by the method in Example 1. When the oriented pore direction was parallel to the incident direction of the sound wave, the sound absorption coefficient varied with the frequency band. The aerogel sound absorption coefficient reached above 0.2 from 1300 Hz, and the absorption peak appeared at 3150 Hz.
[0051] Comparative Example 2
[0052] The other conditions were the same as those in Comparative Example 1, except that the direction of the oriented pores of the aerogel was made perpendicular to the incident direction of the sound wave when testing the sound absorption coefficient.
[0053] according to Figure 3 It can be seen that when the oriented holes are perpendicular to the incident sound wave, the chance of the sound wave entering the aerogel is reduced, the sound absorption performance in the medium and low frequency bands is reduced, and the absorption peak moves to the high frequency and appears at 5000 Hz.
[0054] From Comparative Examples 1 and 2, it can be seen that without adding electrospun barium calcium zirconate titanate wire, when the oriented hole direction is parallel to the incident direction of the sound wave, it has good sound absorption performance in the full frequency band. However, when the oriented hole is perpendicular to the incident sound wave, the absorption peak will move significantly to the high frequency.
[0055] Comparative Example 3
[0056] Take 10 ml of polyvinyl alcohol aqueous solution and pour it into a circular mold with a height of 5 mm. When the hot and cold plates drop to -100°C, place the mold on the hot and cold plates and freeze for 30 minutes to obtain a white columnar frozen block. After the mold is removed, place the frozen block at -50°C and freeze-dry under a vacuum of 10Pa for 72 hours to obtain an oriented porous polyvinyl alcohol sound-absorbing aerogel.
[0057] Figure 4 The curve of the sound absorption coefficient changing with the frequency band is the curve of the aerogel prepared by the method in Example 3, when the oriented pore direction is parallel to the incident direction of the sound wave. It can be seen that the aerogel prepared using only polyvinyl alcohol has poor sound absorption performance, and the sound absorption coefficient of the highest absorption peak is only 0.481.
[0058] Example 1
[0059] 15 mL of acetic acid and 15 mL of ethylene glycol methyl ether were mixed in a conical flask, and then 0.5285 g of calcium acetate monohydrate, 4.34214 g of barium acetate, and 0.97532 g of zirconium acetylacetonate were added thereto, and the mixture was stirred for 3 h at 90 °C until the solution was clear, thereby obtaining liquid A. 4.0044 g of acetylacetone and 6.12576 g of tetrabutyl titanate were mixed in a beaker, and stirred for 20 min at 45 °C, thereby obtaining liquid B. Liquid B was added to liquid A, and stirred at 45 °C for 6 h, and then allowed to stand at room temperature for 12 h. If the sol was clear and bright at this time, calcium zirconate titanate barium sol was obtained.
[0060] Take 10mL of barium zirconate calcium sol and add 0.55g of polyvinyl pyrrolidone to it, stir it thoroughly under heating conditions at 40℃ until the polyvinyl pyrrolidone is completely dissolved to obtain a spinning solution. Then add the spinning solution to the 10mL syringe of the electrospinning feed, adjust the distance between the spinning receiving roller and the needle to 10cm, select the feeding speed to be 1mL / h, the electric field applied at the needle is 10kV, the receiving roller speed is 800r / min, the spinning humidity is adjusted to 20%, and the spinning temperature is 40℃. The barium zirconate calcium sol is ejected from the needle under the action of the electric field and collected by the receiving roller. At the end of electrospinning, the next layer of electrospun barium zirconate calcium wire film can be peeled off from the receiving roller, and the film can be placed in a 70℃ oven for drying for 24h for standby use. Put the dried electrospun barium zirconate calcium wire film into the crucible, and put the crucible into the sintering furnace. The temperature was raised to 325°C at 3°C / min, kept at this temperature for 1 hour, and then raised to 800°C at 3°C / min and kept at this temperature for 2 hours to obtain barium calcium zirconate titanate ceramic electrostatically spun barium calcium zirconate titanate wire. Figure 5 The SEM image of the electrospun barium calcium zirconate titanate wire obtained is shown in Figure 1. As can be seen from the SEM image, the diameter of the electrospun barium calcium zirconate titanate wire obtained by electrospinning is evenly distributed, the microscopic morphology is straight, and no liquid beads appear.
[0061] Take 0.0415g of electrospun barium calcium zirconate titanate wire, add it to 12g of deionized water, drop 0.01g of polyacrylate, stir for 4h, then add 4.608mL of polyvinyl alcohol aqueous solution, stir for 1h to obtain ceramic slurry. Mix 23.04g of 0.8% bacterial cellulose aqueous dispersion with the ceramic slurry and stir well. The subsequent directional solidification and freeze drying steps are the same as those in Comparative Example 1.
[0062] Figure 6 The aerogel is prepared by the method in Example 1. When the orientation hole direction is parallel to the incident direction of the sound wave, the sound absorption coefficient changes with the frequency band.
[0063] Figure 7 The aerogel is prepared by the method in Example 1. When the orientation hole direction is perpendicular to the incident direction of the sound wave, the sound absorption coefficient changes with the frequency band.
[0064] It can be seen that with the addition of electrospun barium calcium zirconate titanate wire, when the oriented hole direction is parallel to the incident direction of the sound wave, the low-frequency sound absorption effect is better, and when the oriented hole direction is perpendicular to the incident direction of the sound wave, the sound absorption peak moves significantly to the low frequency relative to comparative example 2, and the absorption peak appears at about 4000 Hz. The porous insulating sound-absorbing aerogel of Example 1 can adapt to the absorption of non-directional sound waves.
[0065] Table 1 shows the basic physical properties of the oriented porous heat-insulating sound-absorbing aerogel prepared by the method in Example 1. It can be seen that the aerogel has a higher porosity and a lower density, and its thermal conductivity at room temperature is only 0.051 W / (m·K).
[0066] Table 1
[0067]
[0068] Example 2
[0069] The other preparation processes remained the same as in Example 1, with the only difference being the amount of electrospun barium calcium zirconate titanate wire added being 0.1244 g.
[0070] Figure 8 The aerogel is prepared by the method in Example 1. When the oriented pore direction is perpendicular to the incident direction of the sound wave, the sound absorption coefficient changes with the frequency band. In this Example 2, by further adding electrospun barium calcium zirconate titanate wire, the sound absorption coefficient is further moved to the medium and low frequencies, and the absorption peak appears at about 3000 Hz.
[0071] Table 2 shows the basic physical properties of the oriented porous heat-insulating sound-absorbing aerogel prepared by the method in Example 2. It can be seen that with the addition of electrospun barium calcium zirconate titanate wire, the porosity and thermal conductivity of the aerogel decrease, and its thermal conductivity at room temperature also increases to 0.053 W / (m·K).
[0072] Table 2
[0073]
Claims
1. A porous heat-insulating sound-absorbing aerogel, characterized in that: The porous heat-insulating sound-absorbing aerogel comprises polyvinyl alcohol, bacterial cellulose, and barium calcium zirconate titanate wires, wherein the barium calcium zirconate titanate wires and the bacterial cellulose are entangled with each other and dispersed in the polyvinyl alcohol; In the porous heat-insulating sound-absorbing aerogel, the mass ratio of polyvinyl alcohol: bacterial cellulose: barium zirconate calcium wire is 1-7: 1-5: 1-8; The preparation method of the barium calcium zirconate titanate wire is as follows: polyvinyl pyrrolidone is added to the barium calcium zirconate titanate sol to obtain a mixture, the mixture is subjected to electrostatic spinning to obtain a barium calcium zirconate titanate wire film, and the barium calcium zirconate titanate wire film is sintered to obtain the barium calcium zirconate titanate wire; In the mixture, the solid-liquid mass-to-volume ratio of polyvinyl pyrrolidone to barium calcium zirconate titanate sol is (0.2-0.7) g:10 mL; During the electrospinning, the feeding speed is 0.8-1.5 mL / h; During the electrospinning, the voltage in the electric field is 8 to 15 kV; The sintering system is to first heat the temperature to 280-400°C at a heating rate of 1-3°C / min and keep the temperature for 0.5-2.5h, then heat the temperature to 700-850°C at a heating rate of 1-3°C / min, keep the temperature for 0.5-2.5h, and finally cool with the furnace.
2. The porous heat-insulating sound-absorbing aerogel according to claim 1, characterized in that: The barium calcium zirconate titanate wires are in the shape of short rods, and the bacterial cellulose is in the shape of filaments; The barium calcium zirconate titanate wire is made by electrostatic spinning.
3. The porous heat-insulating sound-absorbing aerogel according to claim 1, characterized in that: The thickness of the porous heat-insulating sound-absorbing aerogel is 5 to 10 mm.
4. A porous heat-insulating sound-absorbing aerogel according to any one of claims 1 to 3, characterized in that: The porous structure of the porous heat-insulating sound-absorbing aerogel is an oriented porous structure.
5. A method for preparing a porous heat-insulating sound-absorbing aerogel according to any one of claims 1 to 4, characterized in that: Calcium barium zirconate titanate wire is added to a solvent, and then a dispersant is added to obtain a mixed solution, a polyvinyl alcohol aqueous solution is added to the mixed solution to obtain a ceramic slurry, and then the ceramic slurry is mixed with a bacterial cellulose aqueous dispersion to obtain a mixed slurry, the mixed slurry is poured into a mold, and then directionally frozen in a directional temperature field, and then freeze-dried to obtain a porous insulating sound-absorbing aerogel.
6. The method for preparing a porous heat-insulating sound-absorbing aerogel according to claim 5, characterized in that: The solvent is selected from at least one of deionized water and anhydrous ethanol; The dispersant is selected from at least one of ammonium citrate, tetramethylammonium hydroxide, ammonium polyacrylate, and polyacrylate; In the mixed solution, the mass fraction of the dispersant is 0.05-0.2%; In the mixed solution, the mass fraction of calcium barium zirconate titanate wire is 0.1-2%.
7. The method for preparing a porous heat-insulating sound-absorbing aerogel according to claim 5, characterized in that: In the polyvinyl alcohol aqueous solution, the mass fraction of polyvinyl alcohol is 3-8%; In the bacterial cellulose aqueous dispersion, the mass fraction of bacterial cellulose is 0.65-0.8%; The mass volume ratio of the mixed solution to the polyvinyl alcohol aqueous solution is 10-15 g: 2-8 mL; The mass ratio of the ceramic slurry to the bacterial cellulose aqueous dispersion is 10-15:20-30.
8. The method for preparing a porous heat-insulating sound-absorbing aerogel according to claim 5, characterized in that: During the directional freezing, the cold end of the directional freezing temperature field is set to -196 to -20°C, the hot end is room temperature, and the directional freezing time is 10 to 30 minutes; The freeze-drying temperature is -60 to 0°C, the vacuum degree is 1 to 100 Pa, and the freeze-drying time is 24 to 72 hours.
9. The use of a porous heat-insulating sound-absorbing aerogel according to any one of claims 1 to 4, characterized in that: The porous heat-insulating sound-absorbing aerogel is used as a sound-absorbing material.